Antioxidant Activities of Extracts from Plants in Minor Uses: Parkia Speciosa, Vitex negundo, and Etlingera elatior - Norasyidah, Harun (2014)
Our country is blessed with a huge number of plant species in our rainforest. According to World Wide Fund for Nature (WWF), the major types of forest in Malaysia are lowland dipterocarp forest, hill dipterocarp forest, upper hill dipterocarp forest and mangrove forest. Among of these abundance of plant sources, there are still a wide number of plants which can be classified as minor use, as they receive little research and therefore information on benefits of the plants are still limited. This current study is to evaluate the antioxidant activity of crude extracts of Parkia speciosa Hassk, Vitex negundo L., and Etlingera elatior Jack. The extraction were using reflux and maceration techniques in two different solubility which are 80% ethanol (aqueous ethanol) and total aqueous. Antioxidant was evaluated initially by thin layer chromatography with 2,2-Diphenyl-1-Picrylhydrazyl (TLC-DPPH) for screening, and quantitatively by DPPH radical scavenging assay and beta carotene bleaching assay with total phenolic and total flavonoid for additional information. Gas chromatography-mass spectrometry (GC-MS) was used for analyzing the volatile compounds existed in all extracts. TLC plate sprayed by DPPH solutions showed a positive reaction, where the yellowish white spot appeared on the purple background. P. speciosa (PSER) extracted in aqueous ethanol by reflux technique shows the best activity for both assays, with EC50 value for DPPH radical scavenging assay of 184.860 μg/mL and 57.595 % for antioxidant activity obtained from beta carotene bleaching assay. PSER also gave the highest value in total phenolic, which is 66.520 μg (GAE)/mg but low in total flavonoids content (TFC), which only 16.975 μg/mL as compared to the highest value showed by ethanolic V. negundo by reflux (VTER) with the value 50.060 μg/mL. These finding suggest that P. speciosa is a potential source of antioxidant that may be increasingly important for human consumption as well as assisting the antioxidant based industries.